Pengaruh Penggunaan Lembar Diskusi Peserta Didik Berbasis Jejaring Pertanyaan terhadap Hasil Belajar Peserta Didik Dalam Pembelajaran Fisika di SMA Negeri 5 Banda Aceh - Farah Nabila; Evendi Evendi; Susanna Susanna (LPPM UNIVERSITAS PGRI SILAMPARI, 2022)
The 2013 curriculum prioritizes the involvement of students who dominate the class during the learning process and the teacher only as a facilitator. In fact, during the process of learning activities students still tend to be passive and lack of enthusiasm for students in participating in physics learning. In order to reduce the problems, efforts are needed that are able to create positive interactions between students and teachers so that they can increase student activity in learning. Efforts are made by using a student discussion sheets based on question web. The purpose of this study was to determine the effect of using student discussion sheets based on question web on student learning outcomes in learning physics at SMA Negeri 5 Banda Aceh. This type of research is an experimental research with a Quasi Experiment design. The research sample was determined by purposive sampling technique as many as 24 students in the experimental class and as many as 24 students in the control class. The data collection technique used is a test technique. The data analysis technique used statistical t test with a significant level of 5% (α = 0.05). The results of data analysis obtained ttable = 1.679 and tcount = 2.768. Therefore, tcount > ttable or 2,768 > 1,679, so that tcount is in the acceptance of Ha and consequently rejects H0. Based on the results of data analysis, it is stated that the research hypothesis is accepted so that it can be concluded that there is a significant effect of using student discussion sheets based on question web on student learning outcomes in learning physics at SMA Negeri 5 Banda Aceh.